2011
DOI: 10.1093/mutage/ger028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose exposure on germline microsatellite mutation rates in humans accidentally exposed to caesium-137 in Goiania

Abstract: A serious radiological accident occurred in 1987 in Goiânia, Brazil, which lead to extensive human and environmental contamination as a result of ionising radiation (IR) from caesium-137. Among the exposed were those in direct contact with caesium-137, their relatives, neighbours, liquidators and health personnel involved in the handling of the radioactive material and the clean-up of the radioactive sites. The exposed group consisted of 10 two-generation families, totalling 34 people. For each exposed family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The ultimate effect of bioaccumulation of 137 Cs in humans, in dependency to the amount ingested, is the development of radiation-induced malignancies, [15][16][17] as well as mutagenesis in germinal cells. 18,19 Many methods are currently available for decontamination of radioactive wastewater from nuclear ssion products. [20][21][22][23][24][25][26][27] However, most of the existing technologies, like co-precipitation, evaporation, reverse osmosis, and ion exchange, show strong disadvantages, with the main ones being low efficiencies, high production and operational costs, or limited reusability.…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate effect of bioaccumulation of 137 Cs in humans, in dependency to the amount ingested, is the development of radiation-induced malignancies, [15][16][17] as well as mutagenesis in germinal cells. 18,19 Many methods are currently available for decontamination of radioactive wastewater from nuclear ssion products. [20][21][22][23][24][25][26][27] However, most of the existing technologies, like co-precipitation, evaporation, reverse osmosis, and ion exchange, show strong disadvantages, with the main ones being low efficiencies, high production and operational costs, or limited reusability.…”
Section: Introductionmentioning
confidence: 99%
“…In total, the competent authorities monitored about 112,000 city residents, although their direct connection with the incident was not established (Rosenthal et al, 1991). About 15 years after the event, a case-control study analyzed the microsatellite mutation rates and found no difference between exposed and unexposed populations (Costa et al, 2011). Other studies have observed high cesium concentration in the subsoil layer of the accident site (Anjos et al, 2002) and indicated that exposure to ionizing radiation can be detected in offspring of exposed individuals (Cruz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%